The patient with epilepsy and medicolegal aspects: a view for the neurologist - Amur FERREIRA NETO SEGUNDO; Maren de Moraes e SILVA; Pilar Bueno Siqueira MERCER; Carolina REINERT; Emerson Faria BORGES; Jacqueline Martins SIQUEIRA; Marina Pazini BOMEDIANO; Maria Carolina Zavagna WITT (Arquivos de Neuro-Psiquiatria)
ABSTRACT Patients with epilepsy face innumerable obstacles in daily life, related to work, permission to drive and interpersonal relationships, which require medical guidance. This paper reports a literature review based on scientific articles and civil and traffic system, as a way to resolve doubts about medical obligations in the patient’s permission to drive and work. An employment agreement requires the contractor to guarantee safety conditions as well as requiring the patient, at the pre-employment medical examination, to let the physician know previous medical conditions, including epilepsy. More than 90% of patients with epilepsy omit this information during the application assessment, thus being subject to imputation of ideological falsehood crime as disposied on article 299 of Brazilian Penal Code. Medical confidentiality breaches may only occur in specific situations. In Brazil, the authorization and driver’s license renewal is governed by the Brazilian Traffic Code (Federal Law n° 9503/1997). For patient evaluations, two groups are considered: those on antiepileptic medication and those on medication withdrawal. A favorable report from the attending physician is also required, in both categories. Seizures that occur exclusively during sleep, and focal aware events or prolonged aura are not differentiated from other seizure types disposed in the traffic law. It is the responsibility of the attending physician to analyze each patient individually to resolve conflicts between public safety and the individual patient’s independence. A frank and honest doctor-patient relationship is essential for the patient to understand the public and individual consequences of epileptic seizures and to feel comfortable seeking medical help.